2021
DOI: 10.1097/scs.0000000000008353
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Intravenous Dexmedetomidine and Acetaminophen for Improved Postoperative Pain Management in Primary Palatoplasty

Abstract: Objective: Suboptimal pain management after primary palatoplasty (PP) may lead to complications such as hypoxemia, and increased hospital length of stay. Opioids are the first option for postoperative acute pain control after PP; however, adverse effects include excessive sedation, respiratory depression, and death, among others. Thus, optimizing postoperative pain control using opioid-sparing techniques is critically important. This paper aims to analyze efficacy and safety of combined intravenous (IV), dexme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“… 2 , 3 , 4 A study demonstrated that intraoperative intravenous dexmedetomidine and acetaminophen during primary palatoplasty provided safe and effective perioperative pain control, resulting in a significantly decreased need for postoperative pain relief. 5 Dexmedetomidine can also aid in suppressing bleeding after thyroidectomy by reducing coughing and emergence agitation. 6 Additionally, it can reduce shivering 7 and also prevent shivering during spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 A study demonstrated that intraoperative intravenous dexmedetomidine and acetaminophen during primary palatoplasty provided safe and effective perioperative pain control, resulting in a significantly decreased need for postoperative pain relief. 5 Dexmedetomidine can also aid in suppressing bleeding after thyroidectomy by reducing coughing and emergence agitation. 6 Additionally, it can reduce shivering 7 and also prevent shivering during spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%